Konsep Fotovoltaik Terintegrasi On Grid dengan Gedung STT-PLN - Aas Wasri Hasanah; Rinna Hariyati; Muchamad Nur Qosim (Energi & Kelistrikan, 2019)
Entering the 21st century, oil and gas supplies are running low. While the need for energy is increasing, especially in industrialized countries, it will increase to 70% between 2000 and 2030. In 2017, the electricity needs will reach 25.4 trillion kWh. Solar energy that can be generated for the entire Indonesian mainland which has an area of ​​± 2 million km2 with a radiation distribution of 4.8 kWh/m2/day is 5.10 mW, equivalent to 112,000 gWp. In terms of technique in totality it can be said that it is feasible to operate, solar panels have an efficiency increase of 17.4%. In terms of components and regional quality that will be absorbed by PLTS and synchronized by KWH EXIM, from calculations with a performance ratio yielding 81%, so the system is technically said to be feasible to be realized.